Coaxial Spring-Like Stretchable Triboelectric Nanogenerator Toward Personal Healthcare Monitoring - Liu, Jinmei; Li, Saixuan; Yang, Maosen; Wang, Yuxin; Cui, Nuanyang; Gu, Long (Frontiers in Bioengineering and Biotechnology, 2022)
Stretchable triboelectric nanogenerators have attracted increasing interests in the field of internet of things and sensor network. Therefore, great efforts have been made to realize the stretchability of electronic devices via elaborated material configurations and ingenious device designs. In this work, a flexible and stretchable TENG is developed with coaxial spring-like structure. The unique structure allows it to generate electrical energy for different degrees of stretching deformations. Its output demonstrates good response to the strain and frequency of the mechanical deformation. At the same time, it exhibits excellent stability and washability. The TENG can be attached on human fingers, elbow, and knee to monitor the body activities. Furthermore, a self-powered temperature sensor system is fabricated by integrating the TENG with a temperature sensor to identify the operating ambient temperature in real time. Combination this flexible and stretchable TENG with body motions and a temperature sensor bring a novel insight into wearable functional electronics and user-friendly heath monitoring, which has important basic research significance and practical application value in biometric systems.